Financial Performance Analysis in Achieving Good Governance at Kandow General Hospital Manado - Freddy Semuel Kawatu; Cecilia Lelly Kewo (AIBPM Publisher, 2021)
The financial performance of the Regional Public Service Agency describes the financial performance report and work performance in a certain period. This research investigates how the financial performance of the Central General Hospital Kandou Hospital and how to reform financial management to achieve good governance? This study applied descriptive qualitative methodology. The field observation was conducted by direct observations on the operational process of the financial accounting section monitors at the Kandou General Hospital. The data was collected by observations and interviews on the hospital leaders, employees, and other stakeholders. The secondary data served as a comparison material obtained from financial performance reports. Through the analysis of financial ratios based on the BLU Financial Performance Indicators, the weighting results indicate that the financial performance values of Kandou Hospital are classified as Healthy (Good).